Aid and sanctions - Kenneth Kletzer (University of California, Economics Department, 2005)
Foreign aid donors and recipient governments often have conflicting objectives. Foreign donors may attempt to influence the policies of recipient governments by offering aid or threatening to suspend aid to sovereign states. This paper considers the credibility of such inducements and the conditioning of aid flows on policy behavior by national governments in the presence of opposing objectives. Aid can be conditioned on past policy actions of the recipient and used to influence the distribution of government resources in a simple repeated agency model. In equilibrium, aid flows are backloaded and reward recipient governments for donor-preferred policy actions. The model is extended to a stochastic setting to allow for asymmetric information between donors and recipients regarding government resources and accumulation of private of foreign assets. This allows for unobserved capital flight implicitly financed by foreign aid inflows by constituents favored by the government. Conditional aid is still feasible and can be enforced by aid suspensions in the presence of potential capital flight.
Keywords: F0; F3; F35; F34; 330; Entwicklungshilfe; Sanktion; Kapitalflucht; Theorie